Do tornadoes really twist? questions and answers about tornadoes and hurricanes - Berger, Melvin; Berger, Gilda; Bond, Higgins (New York : Scholastic, 2000)
Provides answers to a variety of questions about tornadoes and hurricanes, including "Where do most tornadoes strike," and "How long do hurricanes last?"
Includes index.
b
Keywords: Tornadoes -- Miscellanea -- Juvenile literature; Hurricanes -- Miscellanea -- Juvenile literature